A CONGESTION CONTROL ALGORITHM FOR THE PLANETARY INTERNET - L.A. Grieco (IFAC Proceedings Volumes, 2005)
This paper proposes a new rate based congestion control algorithm that significantly improves the utilization of planetary links with respect to classic TCP congestion control. Ns-2 simulation results have shown that the proposed algorithm provides significant goodput improvements with respect to New Reno, Reno Sack, Reno Fack, Vegas, and Westwood+ TCP in the presence of RTTs larger than 1s and smaller than 2000s and packet loss probability ranging from 0.0001 to 0.01.
16th IFAC World Congress
Keywords: Congestion control; Planetary Internet; Time-delay systems